Dehydroepiandrosterone supplementation improves reproductive outcomes in women of the POSEIDON IV group - Morán-Orozco, Eugenia Irene; Lezama-Ruvalcaba, Jorge Luis; Paladino-Barquera, Gerardo A.; Salazar-Trujillo, Jose Carlos; Laguna-Pérez, David Alejandro; Salazar-López Ortiz, Carlos G.; Hidalgo-Carrera, Jaime Antonio (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The decrease in ovarian reserve has become one of the main causes of infertility. Recent studies have sought to improve the reproductive outcomes of these women through adjuvant treatments. In patients undergoing assisted reproduction treatments, exogenous Dehydroepiandrosterone (DHEA) or prasterone acts as a precursor to testosterone in the follicular fluid, which increases steroidogenesis and the number of primary and antral follicles. Methods: A quantitative, quasi-experimental case series study was carried out in the clinical area of assisted reproduction from August 2021 to March 2022. All women included were over 34 years and categorized as POSEIDON IV. They were supplemented with 100 mg of DHEA one month prior to the follicular capture. Data was collected from the records of the patients who met the inclusion criteria, including the antral follicle count on the first three days of the menstrual period before the supplementation and one month after. Finally, the number of metaphase II oocytes and blastocysts obtained were analyzed. Results: There were 22 women underwent controlled ovarian stimulation; there was a difference in antral follicle count from 5±2.1 SD to 8.23​±4.29 SD (p=0.004) and MII oocytes 3.25±2.31 to 4.53±3.27 (p=0.04) before DHEA and after DHEA, respectively. Conclusions: DHEA or prasterone supplementation can be used as an adjuvant treatment in women of the POSEIDON IV group one month before the ovarian stimulation to improve their reproductive outcome.